Observations and Numerical Simulation of Storm Surge during Typhoon Kajiki (August 2025) - Cuong, Nguyen Kim; Thuy, Nguyen Ba; Van Tien, Pham; Hai Dang, Vu; Manh Ha, Bui; Ngoc Tien, Duong (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1SDO - 10.25073/2588-1094/vnuees.5391, 2025)
In this study, the storm surge associated with Typhoon No. 5 (Kajiki, August 2025) was analyzed using both observational data and numerical model simulations. Observational data from the Hon Ngu and Hon Dau oceanographic stations were selected for analysis. The simulations were conducted using the SuWAT model, an integrated numerical system that couples tides, wind waves, and storm surge processes. The results indicate that at the Hon Ngu station, the observed water level reached 3.99 m, with a maximum storm surge of 2.31 m - the highest value recorded over the past 30 years. At the Hon Dau station, although located far from the typhoon center, the maximum storm surge still reached 0.63 m. The maximum surge at Hon Ngu occurred when the typhoon center was approximately 80 km offshore, whereas at Hon Dau it happened when the typhoon center had moved about 50 km inland. At Hon Ngu, the surge induced solely by atmospheric pressure reduction was approximately 0.5 m; however, it occurred after the peak total surge.